Introduction: Louisa May Alcott, Love Lessons - Martha Saxton (European Journal of American Studies)
Louisa May Alcott wrote about love in one form or another for most of her life. She considered its potential to ennoble as well as to deform. She explored its expression between heterosexuals and same sex couples, boys and girls, parents and children. She considered the disguises lovers might adopt as well as their blind spots. She struggled to define a love that diminished neither partner and that morally improved each, as well as the world they inhabited. Over time, she came to see sacrifice as essential to the kind of love she thought true.Alcott, love, marriage, sacrifice, compensation